Struktur dan Komposisi Vegetasi di Habitat Cemara Laut (Casuarina equisetifolia L.) pada Tiga Kawasan Konservasi di Provinsi Bengkulu - Albert Farma; Agus Hikmat; Rinekso Soekmadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Sheoak (Casuarina equisetifolia L) is a species of monotypic taxa that has grown naturally in coastal Bengkulu Province. However, the various dynamics occurring in the coastal areas have disrupted the habitat of this species, affecting the structure and composi-tion of the vegetation. This research aims to analyze the structure and composition of vegetation in sheoak habitat in three conser-vation areas. The vegetation data was collected by line transect plot method. The analysis shows that sheoak stands form an invert-ed curve J in three conservation areas although they were not perfect due to the low density of poles which can be caused by dis-turbances that come from nature and human activity. Vegetation composition in sheoak habitat was composed by 36 species of 27 plant families consisting of shrubs and trees. Sheoak dominated the three areas only at the rate of tree growth while the growth rates of seedlings, saplings and poles were dominated by nyamplung (Calophyllum inophyllum) so the dominance of sheoak can be replaced with nyamplung. Sheoak also supported better habitat for other plant species to grow that showed diversity index value 1.4 to 1.9.